Is a compact organization important for defensive success in elite soccer? - Analysis based on player tracking data - Forcher, L.; Forcher, L.; Altmann, S.; Jekauc, D.; Kempe, M. (International Journal of Sports Science & Coaching, 2023)
The interest in tactical analysis in soccer has increased in the latest years, especially with the growing availability of player tracking data. With it, the defending team's compact organization, which is considered by practitioners to be an important factor in defense, was repeatedly examined. However, the connection between this defensive principle of play and the defending success remains unclear. Therefore, this study aims to investigate the relation of the principle of playing defensive compact organization to the success of the defense. Based on tracking and event data of 153 games of the German Bundesliga (season 2020/21), the compactness (surface area, spread of the team, and of defending subgroups) and the organization (distances between formation lines) of the defending team was compared between successful and unsuccessful defensive plays. There were almost no differences in the compactness of the whole team, and the organizational measures between successful and unsuccessful defensive plays. The defending subgroup of five defenders closest to the ball showed a higher compactness (smaller surface area and smaller spread) in successful defensive plays compared to unsuccessful ones (-0.08 = d = -0.16). Our results indicate that the compactness of players in areas close to the ball seems crucial for defensive success. However, the compact organization of the entire team does not seem important to regain the ball in defense.